Attack on Titan. Before the fall. 5 - Isayama, Hajime, 1986- (Kodansha Comics, 2015)
"Saved from exile, Kuklo and Cardina meet the hero Jorge Pikale, the first man ever to defeat a Titan in combat, and they learn how he did it: a mysterious gas-powered grappling machine known only as "the device." Jorge believes Kuklo might just have the agility and reflexes to master this startling weapon and take the Survey Corps to a new level. But Kuklo has his doubts, and what will Sharle think?"--